Observation of the Kinetic Inductance Limitation for the Fundamental Magnetic Resonance in Ultrasmall Gold v-Shape Split Ring Resonators - Tobing, Landobasa Y. M. (2017)
The achievable fundamental magnetic resonance in split ring resonators (SRR) is limited by the electron plasma oscillation in the metal. This so-called kinetic inductance limitation was predicted many years ago, but its experimental verification has been hindered due to nanofabrication challenges. Here, the first experimental demonstration of magnetic resonance frequency saturation is reported at 520 THz in ultrasmall v-shape gold SRRs.